Doing Internet research with hard-to-reach communities: methodological reflections on gaining meaningful access. (December 2020) - Kaufmann, Mareile; Tzanetakis, Meropi
This article contributes to scholarship on digital sociology by addressing the methodological challenge of gaining access to hard-to-reach online communities. We use assemblage theory to argue how collaborative efforts of human participants, digital technologies, techniques, authorities, cultural codes and the human researcher co-determine aspects of gaining access to online subjects. In particular, we analyse how credibility and reflexivity are assembled in an online research context. This is exemplified by our own experiences of researching hackers that dispute surveillance and the social embeddedness of darknet drug market users. In this article, we demonstrate the utility of an assemblage perspective for understanding the complexities involved in negotiating access to hard-to-reach communities in digital spaces.